Tumor Targeting Using Anti–Epidermal Growth Factor Receptor (ior egf/r3) Immunoconjugate with a Tetraaza Macrocyclic Agent (DO3A-EA) - Gauri Mishra; Puja Panwar; Anil K. Mishra (Molecular Imaging)
Epidermal growth factor receptor (EGFR) signaling inhibition represents a highly promising arena for the application of molecularly targeted cancer therapies. EGFR conjugated metal chelates have been proposed as potential imaging agents for cancers that overexpress EGFR receptors. Through improved understanding of EGFR biology in human cancers, there is anticipation that more tumor-selective therapy approaches with diminished collateral normal tissue toxicity can be advanced. We report here on the results with a thermodynamically stable chelate, 1,4,7-tris(carboxymethyl)-10-(2-aminoethyl)-1,4,7,10-tetraazacyclododecane (DO3A-EA) and anti-EGFr (ior egf/r3) conjugate to develop immunospecifc imaging agent. Conjugation and labelling with anti-EGFr was performed using standard procedure and subjected to purification on size exclusion chromatography. The conjugated antibodies were labeled with a specific activity 20-30 mCi/mg of protein. Labeling efficiencies were measured by ascending paper chromatography on ITLC-SG strips. Radiolabeling of the immunoconjugate was found to be 98.5 ± 0.30%. 99m Tc-DO3A-EA-EGFr conjugate was studied in athymic mice bearing U-87MG, MDA-MB-468 tumors following intravenous injection. Pharmacokinetic and biodistribution studies confirmed long circulation times (t 1/2 (fast)= 45 min and t 1/2 (slow)=4 hours 40 min) and efficient accumulation in tumors. Biodistribution studies in athymic mice grafted with U-87MG human glioblastoma multiforme and Hela human cervical carcinoma tumors revealed significant localization of 99m Tc-labeled antibodies conjugate in tumors and reduced accumulation in normal organs. This new chelating agent is promising for immunoscintigraphy since good tumour-to-normal organ contrast could be demonstrated. These properties can be exploited for immunospecifc contrast agents in nuclear medicine and SPECT imaging.